Component-Based Software Metrics: A Review - Parul; Singh, Dr. Rajender (Innovative Research Thoughts, 2018)
Component Based Software Development (CBSD) has been considered a trending technique for software development. This technique focuses on reducing complexity, development time and error factor of software. There are number of software development techniques available but complexity is major issue. Software metrics are capable to play significant role in measuring the complexity of software. Metrics also help in enhancing the quality of software, supporting the developers for finding risks and suggest actions to be performed. In this paper, various component based software metrics reported by various researchers have been reviewed and addressed the issues for future enhancements.